2007
DOI: 10.1007/s11065-007-9046-6
|View full text |Cite
|
Sign up to set email alerts
|

Cortical Language Mapping in Epilepsy: A Critical Review

Abstract: One challenge in dominant hemisphere epilepsy surgery is to remove sufficient epileptogenic tissue to achieve seizure freedom without compromising postoperative language function. Electrical stimulation mapping (ESM) of language was developed specifically to identify essential language cortex in pharmacologically intractable epilepsy patients undergoing left hemisphere resection of epileptogenic cortex. Surprisingly, the procedure remains unstandardized, and limited data support its clinical validity. Neverthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
118
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(119 citation statements)
references
References 75 publications
(106 reference statements)
1
118
0
Order By: Relevance
“…29,30 It has long been recognized that cortical stimulation can affect function at a distance, 7 and that ESM does not always predict postoperative language outcomes. 10,26,31 This concern is perhaps best illustrated in somatosensory and motor cortices, where the effects of lesions are more predictable.…”
Section: Region Of Interest (Roi) Analysis For Each Patient We Per-mentioning
confidence: 99%
See 2 more Smart Citations
“…29,30 It has long been recognized that cortical stimulation can affect function at a distance, 7 and that ESM does not always predict postoperative language outcomes. 10,26,31 This concern is perhaps best illustrated in somatosensory and motor cortices, where the effects of lesions are more predictable.…”
Section: Region Of Interest (Roi) Analysis For Each Patient We Per-mentioning
confidence: 99%
“…3 The current gold standard, electrocortical stimulation mapping (ESM), is time-consuming 4,5 and often induces afterdischarges or seizures. 4,6,7 Additionally, it is difficult to rule out distant effects through diaschisis or action potentials evoked by stimulation. [7][8][9] These limitations have long motivated the investigation of passive electrocorticographic (ECoG) recordings as a tool for rapidly and safely mapping cortical function prior to resective surgery.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Approximately 35% of patients suffering from focal epilepsy have refractory epilepsy for which curative surgery may be considered (see Noachtar et al, 2003;Kahane, 2004 for a review of eligibility criteria for epilepsy surgery) if the EZ can be identified clearly and removed safely . Major functional regions must be spared to prevent postoperative cognitive deficits (see Hamberger, 2007 for a review). After clinical exploration and video-EEG recording of seizures, an assessment of hemispheric dominance with respect to language and memory is necessary before surgery can be planned (Bookheimer, 2007).…”
Section: Epilepsy and Language Plasticity As Assessed By Neuroimagingmentioning
confidence: 99%
“…58 Postoperative word-finding difficulties are more likely to occur with more extensive resection of lateral temporal cortex, 29 which is one area that stores semantic knowledge. 24 Other predictors of postoperative word-finding difficulties include an absence of hippocampal sclerosis or other imaging abnormalities before surgery, 11 MR tractography showing more lateralized white matter tracts in the language-dominant hemisphere, 48 fMRI temporal lobe laterality index, 51 the absence of risk factors for seizures (for example, febrile seizures in childhood), 56 cessation of language in tissue to be resected during intraoperative electrical stimulation mapping, 23 and better presurgical naming ability. 10 Semantic knowledge acquired later in life is the most vulnerable to loss after surgery.…”
Section: Language After Left Atrmentioning
confidence: 99%